Ripper : the secret life of Walter Sickert - Cornwell, Patricia Daniels (Thomas & Mercer, 2017)
Examines the century-old series of murders that terrorized London in the 1880s, drawing on research, state-of-the-art forensic science, and insights into the criminal mind to reveal the true identity of the infamous Jack the Ripper.